GE_GERICHTE P/15785/2020 vom 10. Dezember 2020 - GE Cour de justice (2020)
DÉLIT CONTINU;OPPOSITION(PROCÉDURE);OBSERVATION DU DÉLAI;NOTIFICATION DE LA DÉCISION;AVOCAT | CPP.353; CPP.354; CPP.87; CPP.129; LEI.115